Comparison of Common Bile Duct Dilatation at the Porta Hepatis in Patients with Obstructive Jaundice on Ultrasonography and Magnetic Resonance Pancreatography: Comparison of Common Bile Duct Dilatation in Obstructive Jaundice - Mehr, Shabana; Shahzad, Nadeem; Khan, Shah Zeb; Nawaz, Anum; Gul, Haleema; Khan, Muhammad Irshad (Pakistan Journal of Health Sciences, 2026)
Obstructive jaundice is a frequent clinical issue that, in most cases, is related to choledocholithiasis, strictures, or malignant lesions. Objective: To compare the level of diagnostic accuracy of USG to that of MRCP in identifying CBD dilatation. Methods: There were 165 patients with clinical suspicion of obstructive jaundice, who were enrolled in six months between 1st July 2024 and 31st December 2024. MRCP was used as the reference standard to assess the diagnostic performance of USG. Calculations were made on sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), diagnostic accuracy, and likelihood ratios. The Receiver Operating Characteristic (ROC) analysis was conducted, and age, gender, BMI, and symptom duration were determined post-stratification to assess diagnostic accuracy. Results: The average age of the participants was 52 years, and 57.6% were men. MRCP was positive in 60.6% of patients with CBD, and USG was positive in 54.5% of patients. USG proved to have a sensitivity of 85.0, specificity of 92.3, and PPV of 94.4 and NPV of 80.0, and a general diagnostic accuracy of 87.9 compared with MRCP. Conclusions: USG offers high specificity and accuracy of diagnosis of CBD dilatation and should be used as a primary imaging tool. MRCP is to be used in cases of inconclusive or negative USG when there is high clinical suspicion.